â€œAn Insight on Basic principles of 13C-NMRâ€ - Vora, Nikunj (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn all carbon atoms about 1.1% of all carbon atoms are the C-13 isotope; the rest (apart from tiny amounts of the radioactive C-14) is C-12.Obtaining C-13 spectra is more complex than for proton NMR. This is primarily because of the low isotopic abundance of 13C in nature. C-13 NMR relies on the magnetic properties of the C-13 nuclei.Carbon-13 nuclei fall into a class known as "spin Â½" nuclei for reasons .The effect of this is that a C-13 nucleus can behave as a little magnet. C-12 nuclei don't have this property.